The Law of International Organisations: «Internal» or «International»? A Critical Analysis of the Relevant Practice of the United Nations Codification Organs - Diego Mejía-Lemos (Revista Chilena de Derecho y Ciencia Política)
The main claims of this paper are that the law of international organisations should be regarded as internal in nature and that, in this re-gard, the use of «rules of the organisation» instead of «internal law of the international organisation» by United Nations codification organs does not address the problems that the latter apparently raises and is not based on solid grounds. In particular, the characterisation of the law of international organisations as «internal» can be understood as a corollary of internatio-nal organisations’ legal personality under international law, without preju-dice to the international nature of some of the instruments which contain «rules of the organisation». Indeed, the law of international organisations should be considered to be «internal law», for it applies only to member states qua members, autonomously from the application of «international law», which applies to them qua states parties to a treaty or bound by a custom or principle. Lastly, the characterisation of the law of an internatio-nal organisation, including its «rules», as «internal law» has practical legal consequences, for, as «internal law», no rule of the organisation could be a special rule of international law derogating from the law of treaties or the law of international responsibility.